Mechanical properties of lime–cement masonry mortars in their early ages - Ramesh, Meera (2019)
Lime–cement mortars are often used in restoration of existing buildings (especially twentieth century onward) as well as new constructions, in order to combine the individual strengths of either type of binder. Despite the knowledge that mortars have a significant impact on the non-linear mechanical behaviour of masonry from the earliest moments of construction, literature that systematically quantifies the impact of adding lime to cement mortars, or vice versa is scarce and scattered. This work is therefore focussed on bridging the research gap that exists in lime–cement masonry mortars with regard to their mechanical properties in the early ages (up to 7 days of curing). Five different mix compositions have been studied with 1:3 binder-aggregate ratio and 10% to 75% lime content in the binder, both by volume. Changes in properties like mechanical strength and stiffness along with ultrasound pulse velocity have been quantified, correlated and associated with change in quantity of lime in the binder (by volume) of the mortar. It was found that every 10% increase in the quantity of lime in the binder led to a 14% decrease in mechanical strength and a corresponding 12% decrease in stiffness, at 7 days of curing age. E-modulus was found to evolve faster than flexural strength, which in turn was found to evolve faster than compressive strength. Impact of curing temperature and the concept of activation energy has been addressed for the mix 1:1:6 (Cement:Lime:Sand).